Biofuels and water. Spatial transformation in Piura, Perú - Urteaga Crovetto, Patricia (2017)
The arrival of biofuels companies in the Chira Valley, Piura, Peru, in order to produce ethanol on sugarcane cultivation, intensified the agricultural use of land and water in the mid-2000s. This article analyzes the ecological, political and social transformations that biofuels production brought about in the valley. For that purpose the paper describes the role of the state in promoting biofuels and the concomitant land and water-grabbing processes in the valley. It also explores the consequences it had for local communities and medium-sized and small farmers. Ethanol production in the Chira valley produced a profound space transformation because land and water-grabbing processes for biofuels reinforced social inequalities. Information for this article was gathered from primary and secondarysources. This is a qualitative research. Eighteen interviews were conducted in Piura and Lima.